Characteristics of metal pollution and multi-isotopic signatures for C, Cu, Zn, and Pb in coastal sediments from special management areas in Korea. (March 2023) - Jeong, Hyeryeong; Lee, Yeonjung; Moon, Hyo-Bang; Ra, Kongtae
Abstract: The concentrations and isotopic compositions of carbon (C), copper (Cu), zinc (Zn), and lead (Pb) in coastal sediments were analyzed to identify potential pollution sources. High concentrations of total organic carbon (TOC) and metals were found close to cities and industrial areas. The isotopic compositions of C, Cu, Zn, and Pb tended to decrease as their concentrations increased. Bi-plots between δ 65 Cu and δ 66 Zn showed that the isotopic compositions in most coastal sediments, except sediments around a smelter, were similar to the isotopic compositions of road dust in urban and industrial areas of Korea. Our results suggest that heavy metal pollution in coastal sediments is greatly influenced by the pollution source, such that most metals originate from traffic and industrial activities in the urban environment. This analysis of multiple isotopes provides insights concerning the transport mechanisms and clarifies potential sources of metal contamination in coastal environments. Graphical abstract: Unlabelled Image Highlights: Metal contents and C, Cu, Zn, and Pb isotopes in coastal sediments were analyzed. Contaminated sediments had lighter isotopic compositions of C, Cu, Zn, and Pb. Metal contamination in coastal regions was highly related to traffic activities. Isotopic signatures can be used to manage metal contamination in coastal environment.